Cell phone use among adolescents attempting suicide and its relationship to quality of life and social support. Issue 1 (2nd January 2022) - Ligier, Fabienne; Rolling, Julie; Guillemin, Francis; Kabuth, Bernard
ABSTRACT: Maintaining cell phone contact with adolescents attempting suicide (AASs) may be useful in preventing recurrence. Health-related quality of life and social support are two characteristics involved in suicidality and, potentially, in how cell phones are used. MEDIADO was designed as a cross-sectional study to compare cell phone use, health-related quality of life, and social support in AASs and a control group. AASs (58) were recruited from Emergency or Pediatric departments and matched to school pupil controls (86); all the adolescents were volunteers. The 58 AASs had a mean age of 14.7 ± 1.5; 84% were girls. Both the control group (86) and the AASs use their cell phones for more than seven hours per day (p = 0.08), preferentially for texting or social networking but in different proportions (p = 0.03). Both social support and health-related quality of life are significantly worse for AASs than for the control group (p < .0001 to .03). Like the control group, adolescents attempting suicide use their cell phone for longer when they feel better. In conclusion, MEDIADO highlights the particular relevance of using text messaging to reach AASs, data that could be used for intervention following attempted suicide. The manner in which cell phones are used also seems to be affected by quality of life. It would be interesting to assess social support and quality of life in further research, as indicators of clinical changes following suicide attempts.